Measuring Creativity Stimulation with Cubus - Pires, A.; Alves-Oliveira, P.; Arriaga, P.; Martinho, C. (17th International Conference on Intelligent Virtual Agents: Workshop, 2017)
Creativity has grown to be an extremely desirable ability in most modern societies. However, despite this central role, relatively small efforts have been carried out to develop tools that facilitate activities for creativity stimulation. In this paper, we introduce Cubus, which uses autonomous synthetic characters to stimulate idea generation in groups of children during a storytelling activity. With Cubus, children can invent a story and use the stop-motion technique to create a movie of their story. We provide an overview of the process of Cubus’ system design as well as the methodologies followed in our user studies, which accompanied Cubus’ design from its conceptual phase to its final evaluation.